Atropisomeric Properties of 9-Methyl-1,4-benzodiazepin-2-ones - Tanaka, Ryoko; Makino, Kosho; Tabata, Hidetsugu; Oshitari, Tetsuta; Natsugari, Hideaki; Takahashi, Hideyo (Synthesis, 2021)
The atropisomeric and conformational properties of 1,4-benzodiazepin-2-ones were investigated by freezing the conformation with a methyl group at the C9 of 1,4-benzodiazepine. It was revealed that 1,4-benzodiazepin-2-ones exist only as a pair of enantiomers [(a1R, a2S) and (a1S, a2R)], which was confirmed by X-ray analysis. The absolute configuration of each atropisomer was deduced by comparing the [α]D and CD data with those of (–)-N-methoxycarbonylmethylated 9-methyl-5-phenyl-1,4-benzodiaepin-2-one derivative. It was elucidated that the corresponding N-methylated derivative showed similar CD spectra, although the rotational direction of [α]D was opposite to that of others.
Keywords: atropisomerism; absolute configuration; 1,4-benzodiazepin-2-one; CD spectra; X-ray crystal structure analysis